2006
DOI: 10.1038/sj.cgt.7700971
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of cervical cancer cell growth in vitro and in vivo with lentiviral-vector delivered short hairpin RNA targeting human papillomavirus E6 and E7 oncogenes

Abstract: In this study, we investigated the suppressive effect of a short hairpin RNA delivered by a lentiviral vector (LV-shRNA) against human papillomavirus (HPV) type 18 E6 on the expression of the oncogenes E6 and E7 in cervical cancer HeLa cells both in vitro and in vivo. The LV-shRNA effectively delivered the shRNA to HeLa cells and lead to a dose-dependent reduction of E7 protein and the stabilization of E6 target proteins, p53 and p21. Low-dose infection of HeLa cells with LV-shRNA caused reduced cell growth an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
105
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(111 citation statements)
references
References 42 publications
5
105
1
Order By: Relevance
“…Low-dose E7-shRNA infection of HeLa cells with lentiviral vectorshRNA caused reduced cell growth and the induction of senescence, whereas a high-dose infection resulted in specific cell death via apoptosis. 33 Similar results also have been reported that the Sulindac, a nonsteroidal anti-inflammatory drug (NSAID), induces specific degradation of the HPV oncoprotein E7 and causes growth arrest and apoptosis in cervical carcinoma cells. 34 Even with all these information available, the oncogenic mechanism of E7 still remains elusive basically because the mutant forms of E7 that still maintain complete pRb-binding ability fail to transform cells.…”
Section: Discussionsupporting
confidence: 72%
“…Low-dose E7-shRNA infection of HeLa cells with lentiviral vectorshRNA caused reduced cell growth and the induction of senescence, whereas a high-dose infection resulted in specific cell death via apoptosis. 33 Similar results also have been reported that the Sulindac, a nonsteroidal anti-inflammatory drug (NSAID), induces specific degradation of the HPV oncoprotein E7 and causes growth arrest and apoptosis in cervical carcinoma cells. 34 Even with all these information available, the oncogenic mechanism of E7 still remains elusive basically because the mutant forms of E7 that still maintain complete pRb-binding ability fail to transform cells.…”
Section: Discussionsupporting
confidence: 72%
“…Green fluorescent protein (GFP)-expressing FaDu cells (FaDu-GFP) were established following infection with the GFP-expressing pLL3.7 lentiviral construct as previously described (10,11). Cells were checked at intervals through fluorescence microscopy or fluorescence-activated cell sorting to confirm continued stable expression of GFP.…”
Section: Generation Of Green Fluorescent Protein-expressing Cells Andmentioning
confidence: 99%
“…[8][9][10] Therefore, these two oncogenes are regarded as ideal targets for developing and testing RNAi-based therapeutic treatments. Previous studies, including our own, have demonstrated that silencing HPV E6/E7, with siRNA or short hairpin RNA (shRNA), leads to cervical cancer cells undergoing apoptosis or senescence [11][12][13][14] and inhibition of tumor growth in vivo. [14][15][16][17] These results suggest that RNAi therapy could be developed for cervical cancer treatment.…”
Section: Introductionmentioning
confidence: 99%